Pengaruh Sistem Pengendalian Internal, Asimetri Informasi, Kesesuaian Kompensasi dan Ketaatan Aturan Akuntansi Terhadap Kecenderungan Kecurangan Akuntansi (Fraud) pada Organisasi Perangkat Daerah (OPD) Kota Denpasar - Dewa Ayu Komang Bintani; I.B. Made Putra Manuaba; I Ketut Puja Wirya Sanjaya (Jurnal Widya Akuntansi dan Keuangan, 2026)
Abstract: This study aims to analyze the effect of Internal Control Systems, Information Asymmetry, Compensation Suitability, and Compliance with Accounting Rules on the Tendency of Accounting Fraud in the Regional Government Organizations (Organisasi Perangkat Daerah/OPD) of Denpasar City. The population of this study consists of 126 employees working in the OPD of Denpasar City. Data were analyzed using multiple linear regression analysis. The simultaneous test results indicate that Internal Control Systems, Information Asymmetry, Compensation Suitability, and Compliance with Accounting Rules have a positive and significant effect on the Tendency of Accounting Fraud in the OPD of Denpasar City. Partially, the results show that Internal Control Systems have a negative effect, Information Asymmetry has a positive effect, while Compensation Suitability and Compliance with Accounting Rules have a negative effect on the Tendency of Accounting Fraud in the OPD of Denpasar City.   Keywords: Internal Control Systems, Information Asymmetry, Compensation Suitability, Compliance with Accounting Rules, Accounting Fraud Tendency.